"This Is What a Mechanic Sounds Like": Children's Vocal Control Reveals Implicit Occupational Stereotypes. (August 2020) - Cartei, Valentina; Oakhill, Jane; Garnham, Alan; Banerjee, Robin; Reby, David
In this study, we explored the use of variation in sex-related cues of the voice to investigate implicit occupational stereotyping in children. Eighty-two children between the ages of 5 and 10 years took part in an imitation task in which they were provided with descriptions of nine occupations (three traditionally male, three traditionally female, and three gender-neutral professions) and asked to give voices to them (e.g., "How would a mechanic say . . . ?"). Overall, children adapted their voices to conform to gender-stereotyped expectations by masculinizing (lowering voice pitch and resonance) and feminizing (raising voice pitch and resonance) their voices for the traditionally male and female occupations, respectively. The magnitude of these shifts increased with age, particularly in boys, and was not mediated by children's explicit stereotyping of the same occupations. We conclude by proposing a simple tool based on voice pitch for assessing levels of implicit occupational-gender stereotyping in children.